Development and validation english learning materials based on task-based learning for nursing students - Ahmad Rusli; Jufrizal Jufrizal; Hamzah Hamzah (Jurnal Aplikasi IPTEK Indonesia, 2018)
The aim of this research was to develop English learning materials based on task-based learning in the form of handout for nursing study program students. There are 33 students used as sample and there are 4 experts to judge the development process of developed handout. Instruments of this research are questionnaires, interview, and validation checklist. Research method was Research and Development (R&D). ADDIE model used to develop the handout. The result of needs analysis indicated the students needed to learn English language use in the nursing context. Then appropriate handout of English for Nursing was developed based on the result of needs analysis. Based on the experts’ judgments and users’ perception, the developed handout are categorized valid, effective, and practical.